EMPLOYEE ROLE SATISFATION – A STUDY WITH REFERENCE TO PUBLIC AND PRIVATE SECTOR TELECOM IN VIJAYAWADA, KRISHNA DIST. AP. INDIA (International Journal of Food and Nutritional Sciences, 2022)
This study is based on primary data with of 210 sample respondents 105 each from BSNL and Airtel companies operating at Vijayawada Andhra Pradesh. An attempt is made in this paper to examine the employee role satisfaction at their work place at Bharat Sanchar Nigam Limited (BSNL) and Airtel companies. The objective of this research paper is to present an analysis on role satisfaction in sample organizations. Statistical tools like simple percentages, and Chi-square test were used to analyse the data collected.